Development of soft magnetic composites for magnetized pavement to improve the efficiency of electric vehicle's wireless power transfer - Yue Hou (Journal of Cleaner Production, 2024)
Integrating the wireless power transfer (WPT) system into the pavement is an effective way to solve the inconvenience of electric vehicles (EVs)’ charging, accelerating the growth of ownership of EVs to achieve net carbon zero in transportation. However, the existence of a cement paving layer between coils was a negative impact factor. Here, two types of ferrite powders were separately mixed into the cement to prepare soft magnetic composite (SMC) material to enhance the coupling degree of coils. The magnetic and mechanical performance of the composite were tested by a vibrating sample magnetometer and compressive and flexural strength tester. Furthermore, to explore the optimal layout of the magnetized pavement structure, nine pavement layouts were designed based on the distribution of magnetic flux. Finally, the effect of SMC material on improving the charging performance was verified by WPT system test platform. Results showed that the Ni-Zn ferrite powder exhibited superior magnetic permeability due to its stronger magnetic moments and lower magnetic domain wall energy compared to Mn-Zn ferrite powder. The peak relative permeability of SMC materials reached 14.370 with an equal mass ratio of Ni-Zn ferrite powder to cement. Conversely, optimal strength was attained with a Mn-Zn ferrite to cement ratio of 0.2, resulting in a compressive strength of 36 MPa and a flexural strength of 4.0 MPa. Strategically placing SMC within the pavement, both in the core's interior and exterior to the coil, enhanced the coupling coefficient of coils, thereby improving the transmission efficiency of the WPT system. The incorporation of Ni-Zn ferrite powder in a 1:1 mass ratio to cement materialized the highest efficiency. Nonetheless, considering the mechanical performance, the SMC material with a 0.6 mass ratio of Mn-Zn ferrite powder to cement was recommended for magnetized pavements. The WPT system test results showed a transmission efficiency of 89.78% when utilizing magnetized pavement, surpassing the efficiency with the whole pavement material by 1.36%, which indicated great value and potential in energy conservation and carbon reduction of employing magnetized pavement in WPT technology.